2022
DOI: 10.3390/ani12070878
|View full text |Cite
|
Sign up to set email alerts
|

Shorter Grazing Time and Supplementation Are Beneficial for Gastrointestinal Tract Development and Carcass Traits of Growing Lambs

Abstract: The effects of restricted grazing durations on the gastrointestinal development and carcass quality of growing lambs are poorly understood. In this study, 32 lambs were randomly assigned to four groups (n = 8, body weight = 21.86 kg) corresponding to 2, 4, 8 and 12 h of grazing per day. When off-pasture, all lambs were housed and fed concentrate and hay. When the grazing time decreased from 12 h to 2 h, the abomasum weight and large intestine length decreased (p = 0.019; p = 0.069). Compared to lambs grazed fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
1
0
0
Order By: Relevance
“…Under the same physiological conditions (breed, age, and initial body weight), the G group had lower ADG compared to the T and F groups, due to less DMI and higher ADF content in the diet resulting in the reduced nutrient intake or absorption efficiency. Similar results were also observed in small-tailed Han sheep and Ujumuqin lambs that the final body weight or carcass weight was significantly higher in the confinement group compared to that in the grazing group (Wang et al, 2020;Jin et al, 2022). Our results indicated that the barn feeding strategy can significantly improve the growth performance of Gangba sheep in the F group through the systemic ruminal microbiota-host interactions.…”
Section: E Ects Of Feeding Strategies On Growth Performance Of Gangba...supporting
confidence: 86%
“…Under the same physiological conditions (breed, age, and initial body weight), the G group had lower ADG compared to the T and F groups, due to less DMI and higher ADF content in the diet resulting in the reduced nutrient intake or absorption efficiency. Similar results were also observed in small-tailed Han sheep and Ujumuqin lambs that the final body weight or carcass weight was significantly higher in the confinement group compared to that in the grazing group (Wang et al, 2020;Jin et al, 2022). Our results indicated that the barn feeding strategy can significantly improve the growth performance of Gangba sheep in the F group through the systemic ruminal microbiota-host interactions.…”
Section: E Ects Of Feeding Strategies On Growth Performance Of Gangba...supporting
confidence: 86%